Longitudinal effects of lipid-lowering treatment on high-risk plaque features and pericoronary adipose tissue attenuation using serial coronary computed tomography - Weichsel, Loris; André, Florian; Renker, Matthias; Weberling, Lukas D.; Breitbart, Philipp; Overhoff, Daniel; Beer, Meinrad; Vattay, Borbála; Buß, Sebastian Johannes; Marwan, Mohamed; Baumann, Stefan; Giannopoulos, Andreas; et al. (Diagnostics, 2025)
Aim: To evaluate the impact of different lipid-lowering treatment intensities on high-risk plaque features and pericoronary adipose tissue (PCAT) attenuation in patients undergoing serial coronary computed tomography angiography (CCTA). Methods: Individuals with suspected or known coronary artery disease (CAD) from 11 imaging centers who underwent serial CCTA examinations were retrospectively analyzed. Plaque volumes and PCAT were quantified, and the presence of high-risk plaque features was semi-quantitatively assessed using the plaque feature score (PFS). Results: In total, 216 consecutive patients (mean age 63.1 ± 9.7 years, 26.4% female) were included. The mean observation and treatment timespan between the CCTA scans was 824.5 (interquartile range (IQR) = 463.0-1323.0) days (27.5 months). The regression of high-risk features was more common with high-intensity versus low or no lipid-lowering treatment (HR = 4.6, 95%CI = 1.8-12.0, p < 0.001) and was associated with the attenuated increase in non-calcified plaque volume (p < 0.001). PCATmean decreased with increasing intensity of lipid-lowering treatment (p = 0.01) but no associations were observed between the changes in PCAT and PFS or plaque volumes. Lipid-lowering drug intensity was predictive of PFS regression (p < 0.001), whereas baseline PCATRCA was predictive for PFS progression (p = 0.03), both independent of age, cardiovascular risk factors, and baseline plaque volumes. Conclusions: PCAT predicts the progression of high-risk coronary plaque features. High-intensity lipid-lowering drugs may cause the regression of high-risk plaque features through a plaque ‘delipidization’ process. Future trials are now warranted, studying if this process is potentially associated with improved clinical outcomes.
Gesehen am 29.10.2025